De un pensar racional a un pensar phronético: una idea de educación desde Paul Ricœur (Papeles, 2011)
Nowadays school strives for developing thinking abilities aiming a critical and autonomous reason to build a good responsibility sense. But these efforts have formed selfish and calculating youths. This kind of education takes young people to lose his freedom and his self-identity form the selfish and calculating exercise of his thought abilities. Before this landscape this paper tries to present the Ricœurian concept of Phronesis as one horizon which can guide current education and formed students in freedom and critical thinking in favor of self-realization in community. Phronesis as human capacity and virtue or excellence in acting with and for others, could be the horizon of school labor, one which have as end students guidance under the notion of selfformation and not of being formatted. This self-formation is based in the possibility of knowing oneself, discover oneself in one´s faults or virtues and acting from decision making processes guided by self-reflection and knowledge of one self.
Keywords: Autonomy; critical thinking; identity; school; phrónesis